Conceptual framework to identify and analyze food system innovations that can lead to improvements in the choices available to consumers and their diets - CGIAR Research Program on Agriculture for Nutrition and Health (2019)
The framework was published, presented at conferences. Training how to apply the framework was included as part of this flagship's capacity building efforts. Applying the framework as ongoing efforts to design and test food system innovations with partners in the four focus countries with IFPRI, CIAT, Bioversity, CIRAD and WUR.